NON-STANDARD AFFIXES USED BY INDONESIAN INFLUENCERS ON THEIR INSTAGRAM ACCOUNTS - Maria Bonifasia Ellen Wea Duha (LINGUA LITERA : journal of english linguistics and literature, 2021)
Abstract The use of affixes occurs in several languages in the world. In the Indonesian language, affix is used by people in communication. Affix is often used incommunication in standard or non-standard. Moreover, communication became easier because of the development of online media such as Instagram. In this media, the users that have a high number of followers are called influencers. However, lots of influencers do not use language that suits the standard. For this reason, the writer analyzes the use of language based on the situations correctly. The writer did qualitative research to describe and analyze the variations and functions of nonstandard affixes on Instagram. Later, the writer found that suffix –in was the most used affix by the three influencers compared to other suffixesand also the use of non-standard affixes to simplify the expression of a verb, adjective, an interrogative.